2017
DOI: 10.1021/acscatal.7b03509
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalysis of the Electrochemical Oxygen Evolution Reaction by Iron(III) Ions Adsorbed on Amorphous Cobalt Oxide

Abstract: The oxygen evolution reaction (OER) is the bottleneck in the efficient production of hydrogen gas fuel via the electrochemical splitting of water. In this work, we present and elucidate the workings of an OER catalytic system which consists of cobalt oxide (CoO x ) with adsorbed Fe 3+ ions. The CoO x was electrodeposited onto glassy-carbon-disk electrodes, while Fe 3+ was added to the 1 M KOH electrolyte. Linear sweep voltammetry and chronopotentiometry were used to assess the system's OER activity. The additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
153
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(156 citation statements)
references
References 58 publications
3
153
0
Order By: Relevance
“…[14] Co(Fe)O x H y is structurally and electrochemically similar to Ni(Fe)O x H y . [8] Operando XAS suggests oxidation of Co during the OER to as imilar extent for both samples.F e oxidation was not found in either sample,b ut adsorbed Fe 3+ exhibited alower oxygen coordination and was concluded to be responsible for the higher activity of the sample.U ndercoordinated Fe and Co edge-sites have also been hypothesized to be the active sites in Ni(Fe)O x H y [10,[17][18][19] and CoOOH, respectively. Smith et al examined photochemically deposited Fe 100Ày Co y O x films using operando electrochemical XAS and observed oxidation of Co,b ut not Fe during the OER.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…[14] Co(Fe)O x H y is structurally and electrochemically similar to Ni(Fe)O x H y . [8] Operando XAS suggests oxidation of Co during the OER to as imilar extent for both samples.F e oxidation was not found in either sample,b ut adsorbed Fe 3+ exhibited alower oxygen coordination and was concluded to be responsible for the higher activity of the sample.U ndercoordinated Fe and Co edge-sites have also been hypothesized to be the active sites in Ni(Fe)O x H y [10,[17][18][19] and CoOOH, respectively. Smith et al examined photochemically deposited Fe 100Ày Co y O x films using operando electrochemical XAS and observed oxidation of Co,b ut not Fe during the OER.…”
mentioning
confidence: 94%
“…TheF esites in catalyst films here are well-integrated into the CoOOH structure, evidenced by the similarity of the MÀOa nd MÀMs hell distances in the FT-EXAFS (Figure 4). [8] However in that case no concurrent oxidation of Fe was observed and bond length changes due to Co/Feoxidation during the Co 2+/3+ oxidation wave and during the OER were not separated. [6,8,23,24] Interestingly, our potential-dependent Fe À Ob ond lengths are similar to those of Fe 3+ ions adsorbed on CoO x H y ,r eported by Gong et al,which showed adecrease of the Fe À Obond length from 2.01 to 1.94 when changing the potential from open-circuit to OER conditions.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…These electrochemical characterizations suggest that CoFeNi-O-1 is the best OER catalyst, and its performance is comparable with most recently reported catalysts (Table S6). [16,37] Doping too much Fe into the Co and Ni oxidesr esultsi nt he low catalytic activity owing to the lower OER activity of Fe-rich phases or too much positivec hargeo nt he catalytic sites, which adversely affects the separation of product from the catalyst. These results suggest that the derived CoFeNi-O-1 could be employed as ap romising OER electrocatalyst with high catalytic activity,g ood stability, and facile synthesis.…”
Section: Electrocatalyticp Erformancementioning
confidence: 99%